2021
DOI: 10.1007/s00420-021-01720-z
|View full text |Cite
|
Sign up to set email alerts
|

Impact of different work organizational models on gender differences in exposure to psychosocial and ergonomic hazards at work and in mental and physical health

Abstract: Purpose To examine differences between genders in exposure to psychosocial and ergonomic factors at work and in work-related health, according to different work organization models. Methods The study population included a sample of 9749 (women: 37.1%) and 10,374 (women: 39.9%) employees who participated in the 2010 and 2015 European Working Conditions Surveys, respectively. Multiple Correspondence Analysis was applied to work characteristics reported by wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 79 publications
(75 reference statements)
0
5
0
Order By: Relevance
“…However, we found also that gender, marital status, years of teaching experience, and working status had no significant relationships with psychosocial work hazards. This finding was supported by a study that found that according to several work organization models, gender was not significantly connected to exposure to psychosocial elements at work (Migliore et al, 2021). On the contrary, several recent studies did not support that gender, marital status, years of teaching experience and working status had no significant relationship with psychosocial work hazards.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…However, we found also that gender, marital status, years of teaching experience, and working status had no significant relationships with psychosocial work hazards. This finding was supported by a study that found that according to several work organization models, gender was not significantly connected to exposure to psychosocial elements at work (Migliore et al, 2021). On the contrary, several recent studies did not support that gender, marital status, years of teaching experience and working status had no significant relationship with psychosocial work hazards.…”
Section: Resultsmentioning
confidence: 93%
“…However, for both formal and informal teachers, the correlations between exposure to psychosocial work risk variables and the prevalence of work‐related disorders were similar (Gimeno Ruiz De Porras et al, 2017). According to several work organization models, gender was not significantly connected to exposure to psychosocial elements at work and in work‐related health (Migliore et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…A strong correlation was found between psychological occupational risks and the ages of workers (Lee et al, 2021) Psychosocial occupational dangers were not associated with gender, marital status, teaching experience, or employment status. It is supported by a study that found no relationship between gender and workplace exposure to psychosocial components (Migliore et al, 2021). Psychosocial job hazards are largely independent of gender, marital status, years of teaching experience, and working position, according to research conducted over the past decade.…”
Section: Discussionmentioning
confidence: 95%
“…The psychological occupational risks of Malaysian primary school teachers were significantly correlated with their age and gender, according to Alias et al (2020). The gender of employees and their work exposure to psychosocial elements was not significantly associated in a study by Migliore et al (2021). The relationship between high physical demands and relatively significant work-family conflict was found to be strongly correlated with an increase in psychosocial job hazards (Weale et al, 2021).…”
Section: Introductionmentioning
confidence: 83%
“…These risk factors and work-related stress are considered the most complex occupational safety and health issues, given that they affect individuals, organizations and the economy [10] (especially Covid-19, as it creates fear of contact with infection and its subsequent transmission to others, particularly their families), increased workload, lack of recognition by society and the organization, and a sense of powerlessness [11]. The study [12] analysed gender differences in relation to the effects of psychosocial and ergonomic factors at work and work-related health. It concluded that reducing the exposure of working women to work stress can be achieved by reducing monotonous work and improving working conditions.…”
Section: Introductionmentioning
confidence: 99%